Single-cell RNA sequencing reveals the molecular features of peripheral blood immune cells in children, adults and centenarians - Zhong, Jinjie; Ding, Rong; Jiang, Huimin; Li, LongFei; Wan, Junli; Feng, Xiaoqian; Chen, Miaomiao; Peng, Liping; Li, Xiaoqin; Lin, Jing; Yang, Haiping; Wang, Mo; et al. (Frontiers in Immunology, 2023)
Peripheral blood immune cells have different molecular characteristics at different stages of the whole lifespan. Knowledge of circulating immune cell types and states from children to centenarians remains incomplete. We profiled peripheral blood mononuclear cells (PBMCs) of multiple age groups with single-cell RNA sequencing (scRNA-seq), involving the age ranges of 1-12 (G1), 20-30(G2), 30-60(G3), 60-80(G4), and >110 years (G5). The proportion and states of myeloid cells changed significantly from G1 to G2. We identified a novel CD8+CCR7+GZMB+ cytotoxic T cell subtype specific in G1, expressing naive and cytotoxic genes, and validated by flow cytometry. CD8+ T cells showed significant changes in the early stage (G1 to G2), while CD4+ T cells changed in the late stage (G4 to G5). Moreover, the intercellular crosstalk among PBMCs in G1 was very dynamic. Susceptibility genes for a variety of autoimmune diseases (AIDs) had different cell-specific expression localization, and the expression of susceptibility genes for AIDs changed with age. Notably, the CD3+ undefined T cells clearly expressed susceptibility genes for multiple AIDs, especially in G3. ETS1 and FLI1, susceptibility genes associated with systemic lupus erythematosus, were differentially expressed in CD4+ and CD8+ effector cells in G1 and G3. These results provided a valuable basis for future research on the unique immune system of the whole lifespan and AIDs.